2004
DOI: 10.1111/j.1600-0463.2004.apm11207-0810.x
|View full text |Cite
|
Sign up to set email alerts
|

Vasculogenic mimicry

Abstract: The term vasculogenic mimicry describes the formation of fluid-conducting channels by highly invasive and genetically dysregulated tumor cells. Two distinctive types of vasculogenic mimicry have been described. Vasculogenic mimicry of the tubular type may be confused morphologically with endothelial cell-lined blood vessels. Vasculogenic mimicry of the patterned matrix type in no way resembles blood vessels morphologically or topologically. Matrix proteins such as laminin, heparan sulfate proteoglycan, and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
196
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 260 publications
(209 citation statements)
references
References 78 publications
(183 reference statements)
3
196
0
5
Order By: Relevance
“…BMP4 in angiogenesis in melanoma T Rothhammer et al distribute plasma and red blood cells in vivo and in vitro, enabling the tumor to become, at least in part, independent of angiogenesis (Folberg et al, 2000;Hendrix et al, 2003;Folberg and Maniotis, 2004). Vasculogenic mimicry, however, is controversially discussed.…”
Section: Bmp4 In Angiogenesis In Melanoma T Rothhammer Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…BMP4 in angiogenesis in melanoma T Rothhammer et al distribute plasma and red blood cells in vivo and in vitro, enabling the tumor to become, at least in part, independent of angiogenesis (Folberg et al, 2000;Hendrix et al, 2003;Folberg and Maniotis, 2004). Vasculogenic mimicry, however, is controversially discussed.…”
Section: Bmp4 In Angiogenesis In Melanoma T Rothhammer Et Almentioning
confidence: 99%
“…On the other hand, melanoma cells are able to de novo generate microcirculatory channels that are composed of extracellular matrix and lined by tumor cells. This process of formation of non-endothelial cell-lined channels has been called 'vasculogenic mimicry' (Maniotis et al, 1999;Folberg et al, 2000;Folberg and Maniotis, 2004). Several genes like VE-cadherin (vascular endothelial cadherin), laminin 5 g2 chain, TIE-1 (tyrosine kinase with immunoglobulin and EGF factor homology domains) and EphA2 (epithelial cell receptor protein-tyrosine kinase), known to be important in angiogenesis, were also identified to play a role in vasculogenic mimicry (Hendrix et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…These channels constitute the vasculogenic mimicry (VM) and the process is called "vasculogenesis." 3,4 Since its discovery, VM has been described in many kinds of tumors, such as melanoma, 5 synovial sarcoma, 6 rhabdomyosarcoma, 6 osteosarcoma, 7 inflammatory and ductal breast carcinoma 8 and ovarian carcinoma. 9,10 Most of these studies have shown some association between angiogenesis or VM proliferation in relationship with the aggressiveness of the tumor.…”
Section: Introductionmentioning
confidence: 99%
“…In vasculogenic mimicry of the patterned matrix type, 3 highly invasive tumor cells form looping patterns rich in extracellular matrix (ECM) in three-dimensional (3D) culture conditions. 1 Highly invasive tumor cells do not generate these patterns when grown under monolayer conditions or on thin matrix, and poorly invasive tumor cells do not generate these patterns under any culture condition.…”
mentioning
confidence: 99%